ChemInform Abstract: A Novel Example of Double 6‐exo‐trig Heterocyclization: Nitrile Conversion to New Anticancer Active (HeLa Cells) Primary Amine Ionic Liquids. Issue 41 (7th October 2014) - Prodius, Denis; Shah, Hamid Saeed; Iqbal, Jamshed; Macaeva, Anastasia; Dimoglo, Anatoli; Kostakis, George E.; Zill, Nicolas; Macaev, Fliur; Powell, Annie K.
Abstract Derivatives (II) are ionic liquids at room temperature.